Remote Monitoring with Voice Command Control and Image Analysis - Shashank Hegde, Roopa K, Dr. Prabhulingesh K,Rohith Pandith (International Journal of Advanced Science and Technology, 2020)
This paper describes a Remote Monitoring System (RMS) for border areas. This is implemented by providing voice commands through an android smart-phone. The system uses a speech-to-text converter and sends these commands to a Raspberry Pi 3B+, at a Remote Site (RS), which is used to monitor the area in its vicinity. The Raspberry Pi is interfaced to a Movable Monitoring Unit (MMU). The MMU at the RS is connected to a PiCamera and a gas sensor. The persons at the remote site are identified through image analysis by the controller for the video captured by PiCamera. The video stream is sent to the Monitoring Centre (MC). The gas sensor output and camera feed are sent to the android smart-phone for continuously monitoring the RS. The gas sensor output is used to detect the presence of any poisonous gas at the RS. The android smart phone and the computer are available at the MC. This system makes use of an MQTT (Message Queuing Telemetry Transport) protocol and can be used for any applications requiring remote monitoring.